Assessment of risk of type 2 diabetes mellitus among rural population in Karnataka by using Indian diabetes risk score - Ramaiah, Radha; Jayarama, Srividya (International Journal Of Community Medicine And Public Health, 2017)
Background: Diabetes has emerged not only as a major public health problem, but also as a global societal catastrophe. Governments worldwide are struggling to meet the cost of the diabetic care. The proportion of people with diabetes is rapidly increasing in many countries, with the documented increase in low and middle income countries. With this background a study was planned with the objective of assessing the risk of diabetes among adults in a rural area using a simple diagnostic tool. Methods: A community based, cross-sectional study was done among 485 adults aged 20 years and above residing in a rural area of Karnataka. Data collection was done by household survey by direct interview using a pretested, structured questionnaire. The questionnaire had 2 parts with part one of socio-demographic variables and part two made up of Indian diabetes risk score (IDRS) questionnaire. IDRS was developed by Mohan et al and its parameters comprise of 2 modifiable (waist circumference, physical activity) and 2 non-modifiable risk factors (age, family history) for diabetes. Analysis was done with open Epi and Microsoft excel. Results: In the present study, according to IDRS, 14.84% of the study subjects had high risk of diabetes, 73.19% had moderate risk and 11.95% had no/low risk of diabetes. Conclusions: The risk of diabetes among adults is on rise in rural areas. Physical activity likes regular exercises, diet and lifestyle modification are some of the interventions that can reduce the risk of diabetes.